Two Cases of Massively Prolapsed Patent Vitellointestinal Duct - Singh, Sudhir (APSP J Case Rep, 2017)
Patent vitellointestinal duct (PVID) is a benign congrnital anomaly ususally presenting with fecal discharge from the umbilicus. In this report, we describe two cases of PVID presented with massive bowel prolapse through the PVID and signs of intestinal obstruction. Surgery revealed prolapse of the ileal intussusceptum through the PVID. Both of the babies were sucssesfully managed with surgery.